Factors Associated With Eye Fatigue Among Eyelash Artisans In A Home-Based Industry In Sumbang Village - Eky - Susilowati; Syifa Ula Hamidya; Nur - Ulfah; Nasya Adelia Putri; Siti Harwanti (Universitas Tribhuwana Tunggadewi, 2026)
Eye fatigue represents a prevalent occupational health issue among workers who perform tasks requiring high visual accuracy and precision, such as eyelash artisans. Extended periods of close-distance visual work, insufficient lighting, and individual visual impairments can elevate the risk of eye strain and negatively affect work performance. Informal sector workers such as eyelash artisans are particularly vulnerable due to long working hours, repetitive tasks involving small objects, and inadequate workplace lighting. Preliminary observations in a home-based eyelash industry in Sumbang Village, Banyumas Regency indicated that many artisans complained of symptoms such as sore eyes, blurred vision, watery eyes, and headaches during or after work. This study aimed to identify factors related to eye fatigue complaints among eyelash artisans working in a home-based industry in Sumbang Village, Banyumas Regency. An explanatory study with a cross-sectional approach was carried out in August 2025 and involved 51 eyelash artisans selected through total sampling. The independent variables examined were age, refractive disorders, eye rest, duration of work, and lighting intensity, while eye fatigue complaints served as the dependent variable. Eye fatigue was assessed using the Visual Fatigue (VF) questionnaire, and lighting levels were measured with a lux meter. Data analysis included univariate analysis and bivariate analysis was performed using the Fisher exact test. The findings revealed that 86.3% of participants reported experiencing eye fatigue. Significant associations were found between eye fatigue complaints and age (p = 0.033), refractive disorders (p = 0.034), and lighting intensity (p = 0.021). In contrast, eye rest (p = 1.000) and work 7duration (p = 0.080) did not show significant relationships with eye fatigue. In conclusion, age, refractive disorders, and inadequate lighting intensity are key factors contributing to eye fatigue among eyelash artisans. Therefore, improving lighting conditions in the workplace and paying attention to workers’ visual health are crucial efforts to minimize eye fatigue and enhance occupational health in the informal sector. Recommendations for future research include longitudinal studies or controlled interventions that incorporate objective measurements (complete refraction examinations, accommodation amplitude, and work performance metrics) and multivariate analyses to examine the mediating/moderating role of age, refraction, and lighting in triggering eye fatigue.